(untitled) (Innovaciones Educativas, 2023)
The present systematization of experience evaluated the use of a low-cost electric/electronic device, attached to a computer mouse, to facilitate the use of the mouse by elderly people with specific manual motor difficulties, who encounter limitations when performing the double click (they lack sufficient strength to generate the necessary pressing speed). The population observed was 76 adults, aged between 60 and 85 years. The objective of the observation was to analyze the suitability of the new tool to the needs of the participants from a socio-technical and interdisciplinary perspective. Data collection was based on group interviews and surveys. It was found that participants over 70 years of age expressed a preference for the new device over the mouse, while the 60-70 age group expressed a preference for the traditional mouse. This result is consistent with the evidence of difficulty in double-clicking, especially after the age of 70. It is concluded that this difference in the perception of the technical aid (double-click simulator) points out (a) the need for an appropriate segmentation of computer courses for older adults, taking into account as a criterion, for example, the operative skills of the participants; and (b) the importance of carrying out a previous diagnosis of these skills, to determine in which cases to use technical aids and which are the most appropriate.